Management of rTTS associated with PGL using VA-ECMO and surgical resection: a case report - Zhou, Kechun; Liu, Guoliang; Chen, Yi; Lin, Li; Lan, Pin (Frontiers in Cardiovascular Medicine, 2024)
Background: Paraganglioma(PGL) is a neuroendocrine tumor located outside the adrenal gland that can secrete catecholamines. Clinical manifestations include headaches, hypertension, and, rarely, cardiomyopathy. Among these, reverse Takotsubo cardiomyopathy(rTTS) is a rare Takotsubo cardiomyopathy(TTS) associated with a surge in catecholamines.Case introduction: This article reports a case of a hypertensive patient admitted for recurrent dizziness and chest tightness. During treatment, the patient suddenly experienced chest tightness and shortness of breath, followed by refractory cardiogenic shock, and was eventually diagnosed with rTTS. The patient gradually recovered and was successfully discharged after receiving treatments, including tracheal intubation with mechanical ventilation, extracorporeal membrane oxygenation (ECMO), and surgery.The diagnosis of rTTS is significantly aided by the presence of free plasma metanephrines and specific changes observed in cardiac ultrasound. In the treatment of severe rTTS, ECMO can serve as a crucial life support technology. Under VA-ECMO support, early resection of the PGL after accelerated preoperative preparation may be a feasible approach.